Is the Ability of Work Discipline to Moderate the Performance of Employees in the District Election Committee and Serang District Voting Committee as Seen From the Influence of Rewards and Punishment - Izdad Irsyadillah Fauzan; Hamdan Hamdan (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This research is related to the influence of reward and punishment on employee performance with work discipline as a mediating variable on the District Election Committee and Voting Committee in Serang District. The purpose of this research is to determine the effect of reward on work discipline partially, the effect of punishment on work discipline partially, the effect of work discipline on employee performance, the effect of reward on employee performance, the effect of punishment on employee performance, the effect of reward on employee performance through work discipline on the District Election Committee and Voting Committee in Serang District. The respondents in this study were 89 employees. The data collection method used was a questionnaire and analyzed using regression analysis and path analysis. The results of this research show that rewards have a positive and significant effect on work discipline and employee performance, then punishment also has a positive and significant effect on work discipline and employee performance. Apart from that, there is an indirect effect of reward on employee performance through work discipline, and an indirect effect of punishment on employee performance through work discipline.